Analysis of Halal Industry Management from an Islamic Economic Perspective - Rambe, Riswan; Kurniawan, Rahmat; Hutagalung, Muhammad Abrar Kasmin (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
The purpose of halal business, as a part of the processing industry grounded in Sharia principles, is to produce goods that are not only halal but also thayyib—meaning safe, healthy, and of high quality for consumption or use. The concept of halal extends beyond the avoidance of prohibited (haram) substances; it also encompasses aspects of safety, quality, and compliance with procedures related to processing, storage, packaging, transportation, and distribution. Halal is increasingly recognized not merely as a religious notion, but as a comprehensive quality standard. As the halal industry continues to grow both globally and nationally, effective and professional management is required to ensure its sustainability and competitiveness. This study aims to explore the integration between Islamic legal principles and management practices in the development of the halal industry. The research employs a qualitative approach using a literature review method, drawing upon relevant journal articles and the book Discourse on the Theology of Economics and the Halal Industry. The findings reveal that Islam encourages active participation of its followers in various economic sectors—including agriculture, fisheries, plantation management, industry, and trade—while upholding Sharia values. Keywords: halal industry, Sharia-based management, Islamic economics, halal-thayyib, literature review